Narrating the Many Autisms Identity, Agency, Mattering - Stenning, Anna (Taylor & Francis, 2024)
Autism is a profoundly contested idea. The focus of this book is not what autism is or what autistic people are, but rather, it grapples with the central question: what does it take for autistic people to participate in a shared world as equals with other people? Drawing from her close reading of a range of texts, by autistic authors, filmmakers, bloggers, and academics, Anna Stenning highlights the creativity and imagination in these accounts and also considers the possibilities that emerge when the unexpected and novel aspects of experience are attended to and afforded their due space. Approaching these narrative accounts in the context of both the Anthropocene and neoliberalism Stenning unpacks and reframes understandings about autism and identity, agency and mattering, across sections exploring autistic intelligibility, autistic sensibility, and community-oriented collaboration and care. By moving away from the non-autistic stories about autism that have, over time, dominated public conception of the autistic experience and relationships, as well as the cognitive and psychoanalytic paradigms that have reduced autism and autistic people to a homogeneous group, the book instead reveals the multiplicity of autistic subjectivities and their subsequent understandings of oppression. It calls on readers to listen to what autistic people have to say about the possibilities of resistance and solidarity against intersecting currents and eddies of power, which endanger all who challenge the neoliberal conception of Life. A stirring and meaningful departure from atomized accounts of neurological difference,Narrating the Many Autisms ponders big questions about its topic and finds clarity and meaning in the sense-making practices of autistic individuals and groups. It will appeal to scholarly readers across the fields of disability studies, cultural studies, critical psychology, sociology, anthropology, and literature. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.